A legal study of apostasy in Malaysia / Khairul Naim Ahmad Saufy - Ahmad Saufy, Khairul Naim (2016)
Currently Malaysia has been declared as a Muslim nation, but now the community has been shocked with alleged issues of apostates getting rampant in Malaysia. the statement made by the Mufti of Perak regarding a study from a group of Malay professionals which reported that more than 100,000 Muslims in Malaysia have now converted has been taken seriously. The case of ayah Pin, Nor Aishah Bokhari, Nyonya Tahir and Lina Joy are among the case that caught the attention of the community. The increasing number of cases of the apostasy among the Malay- Muslims from time to time raised fears of many people. It was recorded from the year 1999–2003, there were 750 applications to change a name from Muslim to non- Muslim at the National Registration Department (JPN). The rising cases of apostasy can disrupt the peace enjoyed by Muslims if the issue is not resolved correctly. However, we see that there is no clear provision on this apostate either in the religious sense from individual perspective according to the law and procedures associated with. Through observations, there was no uniformity of the law among the states regarding apostasy including the procedure of conversion out of Islam.